THE EFFECT OF USING PLYOMETRIC EXERCISES TO IMPROVE SOME PHYSICAL ABILITIES AND PERFORMANCE IN THE TRIPLE JUMP (HOP, STEP, JUMP) - Bensikaddour, Habib; Benzidane, Houcine; Ahmed Benklaouz, Touati; Mokrani, Djamel (My University, 2015)
The research aims to study the effect of Plyometric exercises to improve some specific physical abilities in triple jump, where researchers used the experimental method due to the nature of the research relevance, and the sample was consisted of students from the Institute of Physical Education and Sports at the University of Mostaganem (Algeria). 44 students aged (19 ± 0.55 years) were selected and divided into two equal groups, the first was the control sample which used the traditional style and the second was the experimental one used plyometric exercises during the lesson to know the achievement of the educational goals of the effectiveness of the triple jump, while the tests used were (the broad jump test from the stability, 10 hop walk with the right foot and 10 other ones with the left foot from sprint, sprint 30 m from the moving start, performance in the triple jump). After the treatment of the results by statistical means, and through these results it have been reached several conclusions of them, Plyometric Exercises to develop some Specific Physical Abilities and performance in the triple jump, under discussion significant difference (*p≤0.05). One of the most recommended by the researcher emphasized the need to use, Plyometric exercises that have been applied in research units within the training curriculum due, with similar studies for the preparation of such exercises and use in the development of the rest of the other games.
Keywords: plyometric, Physical Abilities, performance, triple jump.